WeXel oder Die Musik einer Landschaft Teil 2.1 - Das Weltliche Lied - Ungeradtaktig: Jodler und Jodler-Lied - Ungeradtaktig - deutsch, walter (2021)
Yodel and Yodel-Song in the Lower Austrian / Styrian Wechsel region from the beginning of the 19th century, completed with local research 2001-2019 (especially Schwaigen-Reigen® 2007-2009 - traditional music in 18 alpine huts at the beginning of the alpine pasture in June) and references to other sources. Landscape and social structure of the Lower Austrian / Styrian Wechsel-region: once turnstile of the Austro-Hungarian member-states, today centre of the European Union. For the first time a conscious differentiation between measures in triple metre (3/4) and duple metre (2/4) both with yodels and yodel-songs, thus showing its stylistic influence. This axiom has not ben applied as a musical standard in the academic approach of traditional music so far. •WeXel oder Die Musik einer Landschaft Teil 2.1 - Das Weltliche Lied - Ungeradtaktig: Jodler und Jodler-Lied - Ungeradtaktig: https://e-book.fwf.ac.at/o:1601 •WeXel oder Die Musik einer Landschaft Teil 2.2 - Das Weltliche Lied - Geradtaktig: Jodler, Jodler-Lied, Gstanzl und Tanz - Geradtaktig: https://e-book.fwf.ac.at/o:1602 •WeXel oder Die Musik einer Landschaft Teil 2.3 Register - Das Weltliche Lied : Jodler, Jodler-Lied, Gstanzl und Tanz: https://e-book.fwf.ac.at/o:1603